Let's Prefer the Pain Reducing Intervention, Buzzy or ShotBlocker: A Randomized Controlled Trial - Burcu Aykanat Girgin; Eda Aktaş; Derya Kılınç; Duygu Gözen (Galenos Publishing House, 2020)
INTRODUCTION: The aim of this study was to detect and compare the effects of ShotBlocker and Buzzy methods on pain, fear, and parental satisfaction during intramuscular injection. METHODS: This study was an experimental randomized controlled trial. The sample included 90 children at the ages of 6 and 12 to whom intramuscular injection was administered in the pediatric emergency department of a university hospital. The participants were randomly assigned to ShotBlocker (n=30), Buzzy (n=30), and control (n=30) groups. Child Information Form, Wong-Baker FACES Pain Rating Scale, Children's Fear Scale, and Parental Satisfaction Questionnaire were used to collect the data. RESULTS: ShotBlocker and Buzzy groups had significantly lower pain and fear scores and higher parental satisfaction than control group after the procedure (p=0.0001). The lowest pain and fear score and the highest parental satisfaction score were observed in Buzzy group (p=0.0001). DISCUSSION AND CONCLUSION: Both ShotBlocker and Buzzy methods reduce pain and fear of children during intramuscular injection and increasing satisfaction of their parents. However, when compared to ShotBlocker, Buzzy method is more effective in reducing intramuscular injection-related pain and fear and should be preferred primarily.